Numerical Investigation on the Effect of Flexible Connector Configurations on the Hydrodynamic Behavior of Floating Photovoltaics - Yuhan Li; Xiang Li; Deshen Chen; Xing Chen; Yan Zhang; Ming Sheng; Hongliang Qian (Journal of Marine Science and Engineering, 2026)
During the global transition toward cleaner energy infrastructure, floating photovoltaic (FPV) systems have emerged as a research focus in renewable energy technologies due to their distinctive spatial utilization advantages. This study examines the hydrodynamic performance of a novel FPV system comprising multiple floating modules connected via flexible connectors to a circular frame. Three distinct connection schemes among the floating modules were designed for comparative analysis. To ensure computational accuracy, a numerical model was established and validated against existing experimental data from a 2 × 3 scaled array. Although the validation setup differs from the novel configurations proposed in this study, the results confirm the reliability of the adopted numerical method. Based on this validated model, time-domain analyses were conducted to evaluate the six-degree-of-freedom (6-DOF) motions of the FPV, as well as the dynamic responses of the flexible connectors and mooring system under various wave periods, heights, and directions. The study shows that the motion differences in FPV under different connection schemes are mainly observed in short wave periods and oblique waves. At a wave direction of 45°, the maximum differences in surge and sway motions among the schemes reach 0.2 m. The disparity in mooring tension and connector tension for different connection schemes increases as the wave period decreases and the wave height increases. Specifically, the maximum difference in connector tension attains 10 kN under a wave period of 9 s and a wave direction of 45°, while the peak difference in mooring chain tension reaches 13 kN at a wave direction of 90°. The dynamic responses of the connectors and mooring chains in the second connection scheme are superior to those of the other two schemes. The numerical simulations identify the optimal connection scheme. The results provide theoretical guidance for the design and practical application of FPV system.